The influence of dental restoration depth, internal cavity angle, and material properties on biomechanical resistance of a treated molar tooth. (September 2022) - Babaei, Behzad; Cella, Suelen; Farrar, Paul; Prentice, Leon; Prusty, B. Gangadhara
Abstract: Objectives: To assess the hypotheses that a restored tooth structure for a class II occlusal-distal (OD) cavity can be reinforced by optimizing the cavity geometry and choosing composites with adequate mechanical properties. Methods: A human maxillary molar tooth was scanned, and segmented. The 2D profiles of dentin and enamel were drawn and imported to ABAQUS software. Eighteen restored tooth models with different cavity occlusal depths (OcDs) and internal cavity angles were developed. A semi-circular stone part was used to apply contact loads to the restored tooth model. After setting up the required interactions and boundary conditions, a written Python code was used to automatically assign a wide range of elastic moduli, from 2 GPa to 26 GPa, to the composite restorations, and assign constant material properties to the enamel and dentine. For simplicity, the behaviour of the mechanical material was postulated homogeneous and elastic, while the FE analyses were linearly carried out in this study. Also, the code enabled the FEA software to conduct the stress analyses, determine maximum principal stresses, and record the obtained results. Results: The internal cavity angle formed between the mesial wall and the pulpal floor of the cavity significantly changed the peak maximum principal stress both in the enamel and restoration. The peak stress concentrations were observed mostly at the enamel-restoration interface, with an almost perpendicular orientation to this interface. Regarding the effect of occlusal cavity depth (OcD), the model with the shallowest cavity (OcD = 1.5 mm) represented greater resistance to applied loads than the model with deeper cavities (OcD = 2.0 mm and OcD 2.5 mm). The composite modulus (CM) in the range of 10–18 GPa reduced the maximum principal stress concentrations in the enamel. The lowest result for maximum principal stress was observed in the model with OcD = 1.5 mm, CM = 10 GPa and internal cavity angles = 100°, which was the strongest model against contact loads. Significance: Class II OD cavities with optimal geometry have reduced induced stress levels, thus being able to be more mechanically robust against contact load transmitted by a stone. Cavity geometry designs with obtuse (more than 90°) internal cavity angles were significantly efficient in minimizing peak stress concentrations. The results indicated that for the model with obtuse internal cavity angles, choosing a composite with optimised properties can diminish stress, particularly at the tooth-restoration interface. Furthermore, the shallowest the cavity, the sturdier the restoration was, especially when the interface tooth-restoration laid on enamel and not on dentine. Graphical abstract: Image 1